2021
DOI: 10.3389/fonc.2021.729371
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Peritumoral and Intratumoral Radiomics as Pretreatment Predictors of Atypical Responses to Immune Checkpoint Inhibitor Across Tumor Types: A Preliminary Multicenter Study

Abstract: ObjectiveTo develop and validate a new strategy based on radiomics features extracted from intra- and peritumoral regions on CT images for the prediction of atypical responses to the immune checkpoint inhibitor (ICI) in cancer patients.MethodsIn total, 135 patients derived from five hospitals with pathologically confirmed malignancies receiving ICI were included in this retrospective study. Atypical responses including pseudoprogression (PsP) and hyperprogression disease (HPD) were identified as their definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Directly targeting the endpoint has the advantage of fully appreciating the complexity of the response to immunotherapy. Using either baseline imagings [ 94 ] or longitudinal imagings with delta-radiomics analyses [ 95 , 96 ], several models were proposed with very high performances [ 97 ]. With the advantage of prospectively included, but retrospectively analyzed patients treated with nivolumab, a radiomics signature achieved an AUC of 0.77 in the validation dataset [ 98 ].…”
Section: Radiomics/deep-learning: the One To Unite Them All?mentioning
confidence: 99%
“…Directly targeting the endpoint has the advantage of fully appreciating the complexity of the response to immunotherapy. Using either baseline imagings [ 94 ] or longitudinal imagings with delta-radiomics analyses [ 95 , 96 ], several models were proposed with very high performances [ 97 ]. With the advantage of prospectively included, but retrospectively analyzed patients treated with nivolumab, a radiomics signature achieved an AUC of 0.77 in the validation dataset [ 98 ].…”
Section: Radiomics/deep-learning: the One To Unite Them All?mentioning
confidence: 99%
“…In the context of assessing treatment-related changes, radiomics has been applied for several cancer types including brain, 40,[58][59][60][61] prostate, 42,62,63 lung, [64][65][66][67][68][69] esophageal, 70,71 breast, 42,72 and head and neck. 42,[73][74][75][76] In this section, we first discuss the application of radiomics to identifying and distinguishing typical and atypical responses to treatment, including RN, PsP, and HPD (Fig.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Antunes et al 96 demonstrated the role of a radiomic descriptor quantifying the spatial relationship of the textural pattern gradient in differentiating PsP from glioblastoma multiforme recurrence after chemoradiation. He et al 64 studied the role of baseline CT radiomics across patients with multiple tumor types treated with immune checkpoint inhibitors to predict the risk of PsP and to differentiate it from true progression. They analyzed textural features extracted from both intratumoral and peritumoral regions and found that a combination of features from both regions (AUC, 0.919) could predict the risk of PsP and differentiate it from true progression more accurately than peritumoral (AUC, 0.900) or intratumoral (AUC, 0.891) features alone.…”
Section: Using Radiomics To Predict and Distinguish Typical And Atypi...mentioning
confidence: 99%
See 1 more Smart Citation
“…As of today, there are no reliable, clinically validated biomarkers of PD-HPD. In recent years, a few studies were published investigating suitability of image-based biomarkers for PD-HPD prediction (24)(25)(26). Most of these studies, however, considered only CT-based radiomic signatures.…”
Section: Introductionmentioning
confidence: 99%